Estado de la cesárea en Chile. Riesgos y beneficios asociados a esta intervención - Salinas P., Hugo; Naranjo D., Benjamín; Pastén M., Jorge; Retamales M., Beatriz (Revista Hospital Clínico Universidad de Chile, 2007)
Chile has one of the highest cesarean rates in the World. Many factors contribute to increase its incidence. Medical literature shows us that even though there are differences in neonatal and maternal outcomes among patients that undergo cesarean or vaginal delivery; evidence, besides the contrast in costs, is not concluding. Disparities between the private sector and the National System of Health Services (SNSS) are unquestionable. The application of regulatory rules and the individualized registry of actions, as well as a system of medical auditory could help lower significantly the numbers of cesareans. The actual state of cesarean in the public sector and some private health institutions is shown. The elevated rate of cesareans does not assure good quality obstetric care. Private sector interventions could be causing unsuitable handling of this situation, which is why they should give detailed information of the factorsimplied in their obstetric care and perinatal outcomes obtained in order to evaluate the impact of their interventions.